RANCANG BANGUN SISTEM PENDUDUK NON-PERMANEN KELURAHAN PAGESANGAN BARAT BERBASIS WEBSITE DENGAN METODE SCRUM DAN COGNITIVE WALKTHROUGH - Chandra Adiguna; Royana Afwani; I Gede Pasek Suta Wijaya (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2023)
The difficulties faced by non-permanen resident as immigrants from outside the city are difficult to find boarding house that suits them. There are also difficulties encountered by the village staff in Pagesangan Barat which are due to the large amount of data that needs to be accomodated and handled, the non-permanen resident data are not regulated nicely so that it is easy to lose the data and/or difficult to find the data from certain non-permanent residents. In this final project research, will do design and develop Non-Permanen Resident System with the scope of Pagesangan Barat Village and website-based application to help centralize non-permanent resident data, boarding house, studio and dormitory that exist in Pagesangan Barat. As for the research method used in this research are Scrum method where there are 2 actors who play role in it. Author as Scrum Master and Developer, and staff of Pagesangan Barat Village as the product owner. As for the testing of the system that will be appointed in this Final Project, namely usability testing using the cognitive walkthrough method which aims to find out whether the system that has been built is friendly to new users or not. The average result from this cognitive walkthrough testing method shows that from user Super Admin to complete the task scenario need 659 seconds with 100% completion rate, Admin Kelurahan need 831 seconds with 98.5% completion rate, Pemilik Rumah Hunian Sementara need 233 seconds with 97.2% completion rate, and Penduduk Non-Permanen 267 seconds with 97.8% completion rate.